Staged Common and External Carotid Artery Stenting Followed by Superficial Temporal Artery to Middle Cerebral Artery Bypass - Mulcahy, Michael; Presti, Anna Lo; Veken, Jorn Paul Van Der; Steinfort, Brendan; Assaad, Nazih (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Superficial temporal artery (STA) to middle cerebral artery (MCA) bypass surgery for internal carotid artery (ICA) occlusive disease necessarily requires sufficient external carotid artery (ECA) blood flow. Surgical bypass is therefore precluded if there is common carotid artery (CCA) occlusion. Here we present two such cases: one patient had a CCA occlusion and the other had an ICA occlusion and ECA stenosis. Both had failed medical management, and were therefore treated with angioplasty and stenting of the ECA, followed by STA-MCA bypass. We describe the clinical and radiologic outcomes of these cases, and remark on the potential pitfalls associated with this novel approach.
Keywords: cerebral revascularization; extracranial–intracranial bypass; carotid artery occlusion; cerebral ischemia; carotid stent